Assessment of subclinical left ventricular systolic dysfunction in patients with asymptomatic severe aortic stenosis with preserved left ventricular systolic function by three‐dimensional speckle tracking echocardiography. - Nahar, Nurun; Haque, Tuhin; kabiruzzaman, Mohammad; Khan, Mohammad Abdul Mazid; Choudhury, Sohel Reza; Malik, Fazila‐tun‐nesa (Echocardiography, 2023)
Objectives: Left ventricular dysfunction and remodeling can occur as a result of aortic valve stenosis (AS). Three‐dimensional speckle tracking echocardiography (3D‐STE) can detect early left ventricular myocardial dysfunction even before ejection fraction declines. The purpose of this study was to look at the relationship between various myocardial strain parameters measured by 3D‐STE in asymptomatic severe AS patients from Bangladesh. Methods: This study included 46 patients with asymptomatic severe AS but preserved LV systolic function (mean age 50.11 ± 12.66 years, LVEF 63.78 ± 3.95%, AS group) and 33 healthy subjects with no cardiovascular disease (mean age 48.21 ± 4.53 years, LVEF 65.15 ± 3.13%, control group). 3D‐STE was used to measure left ventricular global myocardial strain parameters such as peak systolic longitudinal strain (PSLS), circumferential strain, radial strain, and area strain. Results: The AS group had significantly thicker interventricular septum and posterior ventricular wall than the control group (1.49 ±.19 cm vs..81 ±.09 cm, p <.001; 1.73 ± 1.71 cm vs..81 ±.10 cm, p =.003, respectively.) In the AS group, the Indexed Aortic Valve Area (AVA) was significantly lower than in the control group. (.29 ±.10 vs. 2.03 ±.18, p <.001, respectively). In terms of LVEF (p =.102), left ventricular end diastolic volume (p =.075), or left ventricular end systolic volume (p =.092), no significant inter‐group difference was found. However, global PSLS (−10.75 ± 2.27 vs. −16.42 ± 2.76, p <.001), circumferential strain (−14.26 ± 3.40 vs. −16.64 ± 2.56, p =.001), area strain (−22.70 ± 4.19 vs. −26.45 ± 9.90, p =.024) and radial strain (32.20 ± 8.77 vs. 41.00 ± 7.52, p <.001) in the AS group were significantly lower than in the control group. Conclusion: Our findings showed reductions in left ventricular global myocardial strains, particularly PSLS in patients suffering from asymptomatic severe AS in Bangladesh; this is consistent with other studies. Reduced area strain, detectable with 3D‐STE, is also consistent with that pattern.